Reconstructing Civil and Criminal Liability Frameworks in Digital Financial Fraud: Integrating Cyber Law, Evidence Systems, and Cross-Border Enforcement Mechanisms - Sitta Saraya; Geofani Milthree Saragih; Nabila Afifah Salwa (Journal of Civil Criminal Law, 2025)
Background: The rapid development of financial technology and the increasing volume of cross-border transactions have led to the emergence of increasingly complex digital financial crimes, involving anonymous actors and exploiting regulatory gaps and jurisdictional differences. This condition poses serious challenges to legal systems, particularly in terms of digital evidence, the attribution of legal liability, and the effectiveness of cross-border law enforcement. Objective: This study aims to reconstruct the framework of civil and criminal liability in digital fraud cases to make it more adaptive, integrated, and responsive to technological developments. Method: The research employs a qualitative socio-legal approach, combining normative analysis of cybercrime regulations, case studies of international digital fraud, comparative analysis of legal systems across countries, and interviews with legal practitioners and fintech regulators. Results: The findings reveal significant legal gaps, regulatory fragmentation across jurisdictions, and weaknesses in electronic evidence systems that hinder effective law enforcement. Additionally, the complexity of actors and technologies within digital ecosystems complicates the accurate attribution of legal responsibility. Therefore, an integrated legal framework is required, incorporating both civil and criminal liability, international regulatory harmonization, and the utilization of technology to enhance law enforcement effectiveness.